Science, technology, and strategic calculation: the contributions of Carlos Matus to Latin American STS - Celeste Viedma (Tapuya, 2024)
This article aims to address the contributions of the Chilean economist Carlos Matus to the field of Latin American Thought in Science, Technology and Development, considered the pioneering STS field in the region. To this end, it focuses on the affinities between Matus’ early writings (1970–1980) and various exponents of the first generation of STS scholars. Two key dimensions are analyzed: the link between dependency, human creativity, and technology as defined by a certain style of development, and strategic calculation as a method of rationalizing political decisions. While the former is an aspect shared by Matus and other PLACTED members, the latter is his specific contribution. Two aspects are considered: the “strategic procedure” as a non-mathematical formalization to estimate political feasibility, and the “quasi-structured” problems as a theorization that attempts to account for social and political reality. The paper concludes that Matus’ significant contribution to the field is strategic calculation, a means of rationalizing decisions and enabling profound social transformations.